2014
DOI: 10.1111/afe.12044
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal flight patterns of Ips typographus in southern Sweden and thermal sums required for emergence

Abstract: Abstract1 The spruce bark beetle Ips typographus is the major tree-killing bark beetle in Eurasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
(66 reference statements)
5
24
0
Order By: Relevance
“…Several forest insect pests have benefitted from climate change and its drivers, such as heat spells and gales [1,11]. Traditional ground surveys are inadequate in locating the very first symptoms by phloem-consuming insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several forest insect pests have benefitted from climate change and its drivers, such as heat spells and gales [1,11]. Traditional ground surveys are inadequate in locating the very first symptoms by phloem-consuming insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Karst. ), have been evident in the course of time, in mid and eastern parts of Europe, as well as in southern Norway and Sweden [9][10][11]. Since the year 2010, with a high accumulated temperature, the European spruce bark beetle (Ips typographus L. (I. typographus)) (Curculionidae, Scolytinae) has also triggered high tree mortality in south and mid parts of Finland, due to two annual generations of the pest [12].…”
Section: Introductionmentioning
confidence: 99%
“…Longer growth periods and increased temperature sums have enabled the development of more sister broods and even the development of the second generation in some summers Wermelinger and Seifert 1999;Öhrn et al 2014). Shorter periods of frozen ground and thunder-storms in the summertime have increased the amount of dead wood in the forests, which favours breeding bark beetles (Eriksson et al 2007).…”
Section: Spruce Pestsmentioning
confidence: 99%
“…Continuous monitoring of population levels and phenological surveys are needed for accurate risk estimates and as a basis for timely advice to forest owners about the best management practices . Logging of trees that are windblown at summertime will be more urgent because the swarming time of spruce bark beetles is longer than it used to be (Neuvonen and Viiri 2015;Öhrn et al 2014).…”
Section: Bark Beetles Attacking Norway Sprucementioning
confidence: 99%
“…For example, Öhrn et al (2014) reported region-specific flight patterns for Sweden and concluded that the understanding of key factors for emergence would facilitate efficient pest management and improve models of population dynamics. In the case of I. typographus, its spring swarming has been intensively investigated by numerous researchers in Europe (Annila 1969, Zumr 1982, Harding & Ravn 1985, Lobinger 1994, Wermelinger & Seifert 1998, Faccoli 2009, Öhrn et al 2014, focussing on the minimum temperature threshold for flight activity and the thermal sums needed for beetle development stages. Most of these studies employ spatially and/or temporally highly resolved data sets for bark beetle development.…”
Section: Introductionmentioning
confidence: 99%